Development of a re‐aeration equation for the simulation of dissolved oxygen in degraded streams. (9th July 2020) - Arora, Sameer; Keshari, Ashok K.
Abstract: Discharge of domestic and industrial wastewater into the water bodies is the prime source of degradation of the freshwater ecosystem. Re‐aeration of the river allows the rejuvenation of river water quality by absorbing oxygen from the atmosphere at the air‐water interface. An accurate estimation of the re‐aeration coefficient helps to determine the assimilative capacity of streams and wastewater management also. This paper aims to develop the re‐aeration equation and its validation by modelling dissolved oxygen of the Yamuna River. Predictive re‐aeration equations are used to identify their applicability to the study area and the new equation is designed using multivariate statistical regression techniques. QUAL2Kw model is used to validate the equation by modelling dissolved oxygen. Results indicate that the developed equation performs better than the predictive re‐aeration equations for the prediction of water quality.